Pengaruh Gaya hidup dan Persepsi Harga Terhadap Keputusan Pembelian pada Produk Tas Lokal Jims Honey di Shopee - Sinta Novita; Dewi Indriani Jusuf (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This research aims to analyze the influence of lifestyle and price perception on purchasing decisions for local bag products of the Jims Honey brand on the Shopee platform. The study is motivated by the increasing trend of online shopping among young consumers, where bags are no longer merely functional items but also a reflection of lifestyle and self-identity. This research employed a quantitative method with a descriptive and multiple linear regression analysis approach. Data were collected through questionnaires distributed to 97 Shopee users who had purchased Jims Honey products. The results show that lifestyle (X₁) has a positive and significant effect on purchasing decisions, with a t-value = 3.248 and a significance level of 0.002 (<0.05). Similarly, price perception (X₂) also has a positive and significant influence, with a t-value = 6.828 and a significance level <0.001. Simultaneously, both variables significantly affect purchasing decisions, with an F-value = 109.128 and R² = 0.699, indicating that 69.9% of purchasing decision variations are explained by lifestyle and price perception. These findings confirm that the more positive a consumer’s lifestyle and price perception are, the higher their tendency to purchase Jims Honey products on Shopee.